PENGARUH CUSTOMER ENGAGEMENT, HUMAN-CENTRIC MARKETING, OMNICHANNEL, DAN WORD OF MOUTH MARKETING TERHADAP PENJUALAN KUR DAN BWU PADA PT BANK NEGARA INDONESIA (PERSERO) TBK KANTOR CABANG MELAWAI RAYA - Kevin Kurnia Aulia (Pasca Sarjana Universitas Satya Negara Indonesia, 2025)
This study aims to analyze the influence of customer engagement, human-centric marketing, omnichannel, and word of mouth marketing on increasing sales of credit products at PT Bank Negara Indonesia (Persero) Tbk, Melawai Raya Branch Office. The research was motivated by the gap between the target and realization of the distribution of People's Business Credit (KUR) and BNI Wirausaha, despite an increase after the implementation of the BNIMove innovation. The research method used is a quantitative approach with a survey design, where primary data was obtained through questionnaires to respondents who are active customers using BNI credit products. Data analysis was carried out using multiple linear regression using SPSS software to test the simultaneous and partial effects of independent variables on the dependent variable. The results showed that all four independent variables had a positive and significant effect on sales increase, with customer engagement and human-centric marketing proving to have a dominant influence compared to other variables. These findings emphasize the importance of a marketing strategy that focuses on consumer experience and needs, the utilization of integrated digital channels, and the role of word of mouth as an effective organic promotional tool. This research provides practical implications for BNI to optimize digital-based marketing strategies and service personalization in an effort to increase the number of new debtors and support the achievement of credit distribution targets in the future.